Triaging ethical issues in the coronavirus pandemic: how to prioritize bioethics research during public health emergencies - Shaw, David Martin (Bioethics, 2021)
Much of the ethical discourse concerning the coronavirus pandemic has focused on the allocation of scarce resources, be it potentially beneficial new treatments, ventilators, intensive care beds, or oxygen. Somewhat ironically, the more important ethical issues may lie elsewhere, just as the more important medical issues do not concern intensive care or treatment for COVID-19 patients, but rather the diversion towards these modes of care at the expense of non-Covid patients and treatment. In this article I explore how ethicists can and should prioritize which ethical issues to deal with, and develop a method of triage for identification and prioritization of ethical issues both in the next public health emergency and in bioethics more widely.